2009
DOI: 10.1007/s00128-009-9670-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Acute Toxicity of Profenofos and Its Effects on the Behavioral Pattern of Fingerling Common Carp (Cyprinus carpio L., 1758)

Abstract: Profenofos, an organophosphate insecticide is acetylcholinesterase inhibitor that has the potential to contaminate the ground water. The 96 h LC(50) value of profenofos was determined in 3-month-old fingerling common carp (Cyprinus carpio) with a body weight 1.04 +/- 0.25 g and a body length 4.25 +/- 0.75 cm at 26 +/- 1 degrees C temperature. Trimmed Spearman-Karber (TSK) software was used for the statistical analysis, which calculated the LC(50) value as 62.4 microg/L for three replicates of the assay. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…28 gün boyunca profenofosa maruz kalan sıçanların karaciğer, böbrek, dalak ve testis dokularında patolojik değişikliklerin olduğu belirlenmiştir [5]. Reddy and Rao [23], yine bu insektisite maruz kalan alabalık solucanlarında (Eisenia foetida) vücutta kopmalar, lezyonlar, hücre bezeleri ve kas parçalanmaları şeklinde çeşitli histolojik ve morfolojik değişiklikler gözlerken İsmail et al [4]'da sazan balıklarında (Cyprinus carpio) denge, hareket ve davranış bozukluklarının meydana geldiğini rapor etmiştir. Farelerde anormal sperm oluşumuna, sperm sayısının ve canlılığının azalmasına [24,25], 16 haftalık wistar sıçanlarında ise seminifer tüplerinde ve lyding hücrelerinde yapısal bozulmalara yol açtığı da rapor edilmiştir [1].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…28 gün boyunca profenofosa maruz kalan sıçanların karaciğer, böbrek, dalak ve testis dokularında patolojik değişikliklerin olduğu belirlenmiştir [5]. Reddy and Rao [23], yine bu insektisite maruz kalan alabalık solucanlarında (Eisenia foetida) vücutta kopmalar, lezyonlar, hücre bezeleri ve kas parçalanmaları şeklinde çeşitli histolojik ve morfolojik değişiklikler gözlerken İsmail et al [4]'da sazan balıklarında (Cyprinus carpio) denge, hareket ve davranış bozukluklarının meydana geldiğini rapor etmiştir. Farelerde anormal sperm oluşumuna, sperm sayısının ve canlılığının azalmasına [24,25], 16 haftalık wistar sıçanlarında ise seminifer tüplerinde ve lyding hücrelerinde yapısal bozulmalara yol açtığı da rapor edilmiştir [1].…”
Section: Discussionunclassified
“…Pamukta, meyve ağaçlarında ve sebzelerde böcekleri ve akarları kontrol etmek amacıyla kullanılır [2,3]. İsmail et al [4]'a göre, zooplanktonlar ve böcekler üzerinde yüksek, balıklarda orta, memelilerde ise düşük düzeyde toksik etkiye sahiptir. Çeşitli araştırmacılar tarafından profenofosun farelerde kromozomal bozukluklara yol açtığı, sıçanların polikromatik eritrositlerinde mikronükleus frekansını artırdığı [5], insan periferal lenfosit hücrelerinde de kromozomal kırıklara, gaplara ve DNA hasarlarına neden olduğu bildirilmiştir [6].…”
Section: Introductionunclassified
“…3, 466À473, http://dx.doi.org/10.1080/02772248.2014 value of 0.58 ppm in H. fossilis (Farah et al 2004), while in Lepomis macrochirus, the LC 50 values of diazinon, chlorfevinifos, and profenofos were calculated as 2.5 ppm, 2.9 ppm, and 300 ppb, respectively (Dembele, Haubruge, and Gaspar 2000;Tomlin 1994). Similarly, acute toxicity of profenofos and triazophos in crucian carp was determined to occur at 0.192 and 8.4 ppm, respectively (Jin et al 2010;Li 1998), whereas, in common carp, acute toxicity of profenofos (LC 50 ) and triazophos (LC 100 ) was determined to be 62.4 ppb and 1 ppm, respectively (Ismail et al 2009;Li 1998). Assis et al (2010) found the LC 50 values for carbaryl and carbofuran as 33.8 and 0.92 mmol/L, respectively, while Boran et al (2007) investigated acute toxicity of carbaryl in Oncorhynchus mykiss and Poecilia reticulate.…”
Section: Acute Toxicity I: Effect Of Profenofos and Triazophos (Organmentioning
confidence: 99%
“…Histopathological alterations can be used as indicators for the effect of various anthropogenic pollutants on organisms and are a reflection of overall health of the entire population in the ecosystem. These Research Article (Open access) histopathological biomarkers are closely related to the other biomarkers of stress since many pollutants have to undergo metabolic activation in order to be able to provoke cellular change in the affected organism (Muhammad Ismail, et al, 2009). The present study was under taken to analyze the impact of chronic concentration of dimethoate in liver of fish, Garra mullya.…”
Section: Introductionmentioning
confidence: 99%